2017
DOI: 10.1161/circep.117.005396
|View full text |Cite
|
Sign up to set email alerts
|

Natural History and Clinical Predictors of Atrial Tachycardia in Adults With Congenital Heart Disease

Abstract: Natural history of AT differed among the most common forms of CHD. Simple clinical parameters, easily obtained by noninvasive means, were independent predictors of AT in adults with CHD. Although risk was negligible in patients without any of these factors, their addition progressively increased AT burden.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
26
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(31 citation statements)
references
References 39 publications
2
26
0
3
Order By: Relevance
“…Avila et al 45 sought to identify factors associated with the development of atrial tachycardia in adults with CHD. In a cohort of 3311 patients presenting with atrial tachycardia, they identified 8 factors independently associated with atrial tachycardia, including univentricular physiology, previous intracardiac repair, systemic right ventricle, pulmonary hypertension, pulmonary regurgitation, pulmonary atrioventricular valve regurgitation, and pulmonary and systemic ventricular dysfunction.…”
Section: Pediatric and Congenital Heart Disease Atrial Arrhythmiasmentioning
confidence: 99%
“…Avila et al 45 sought to identify factors associated with the development of atrial tachycardia in adults with CHD. In a cohort of 3311 patients presenting with atrial tachycardia, they identified 8 factors independently associated with atrial tachycardia, including univentricular physiology, previous intracardiac repair, systemic right ventricle, pulmonary hypertension, pulmonary regurgitation, pulmonary atrioventricular valve regurgitation, and pulmonary and systemic ventricular dysfunction.…”
Section: Pediatric and Congenital Heart Disease Atrial Arrhythmiasmentioning
confidence: 99%
“…Cumulative freedom from SND was estimated using a right-censored Kaplan-Meier curve, constructed with age as time scale. 3 A P value < 0.05 was considered statistically significant. Statistical analysis was performed with SPSS version 24 (IBM Corporation, Armonk, New York).…”
Section: Discussionmentioning
confidence: 99%
“…This may explain the relatively low incidence of dysrhythmias, which may be expected to increase with increasing age, as seen with other CHD types. 3,4 However, in our opinion, this time period represents stable surgical experienceabout 10 years after introduction of the 2-patch technique 2 -and encompasses patients currently entering (early) adulthood, who may be at risk of development of dysrhythmias.…”
Section: Study Limitationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Arrhythmias are frequently encountered in patients with congenital heart disease (CHD; with or without corrective surgery) and respond poorly to pharmacologic therapies. [98][99][100] Catheter ablation is a valuable treatment option but must respond to many challenges with regard to the anatomical variances, type of arrhythmia substrate, and access to the target chamber. 88,[101][102][103][104] In all these patients, a careful review of the entire hemodynamic and arrhythmia situation needs to be performed prior to the procedure and, if available, operation notes need to be reviewed.…”
Section: Chap Ter 6: Us E Of 3d Mapping In Arrhy Thmia S In Cong Enmentioning
confidence: 99%